Answer:
n = -3
Explanation:
Simplifying
11(n + -1) + 35 = 3n
Reorder the terms:
11(-1 + n) + 35 = 3n
(-1 * 11 + n * 11) + 35 = 3n
(-11 + 11n) + 35 = 3n
Reorder the terms:
-11 + 35 + 11n = 3n
Combine like terms: -11 + 35 = 24
24 + 11n = 3n
Solving
24 + 11n = 3n
Solving for variable 'n'.
Move all terms containing n to the left, all other terms to the right.
Add '-3n' to each side of the equation.
24 + 11n + -3n = 3n + -3n
Combine like terms: 11n + -3n = 8n
24 + 8n = 3n + -3n
Combine like terms: 3n + -3n = 0
24 + 8n = 0
Add '-24' to each side of the equation.
24 + -24 + 8n = 0 + -24
Combine like terms: 24 + -24 = 0
0 + 8n = 0 + -24
8n = 0 + -24
Combine like terms: 0 + -24 = -24
8n = -24
Divide each side by '8'.
n = -3
Simplifying
n = -3